ESG SCORING AND EARNINGS MANAGEMENT: SYSTEMATIC LITERATURE REVIEW - Muhammad Arroyyan; Sultan Rafli; Windi Satria Ananda; Hana Maria Natalia Siahaan (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to examine the development of research on Environmental, Social, and Governance (ESG) and Earnings Management practices. The method used in this research is a systematic literature review with a qualitative approach. The data collected are previous articles on Environmental, Social, and Governance (ESG) and Earnings Management in the period 2015 to 2025. The findings of this study thoroughly outline development trends, types of variables used, measurement methods, and provide recommendations for future research directions related to the topics of Environmental, Social, and Governance (ESG) and Earnings Management. The analysis shows that studies on ESG and Earnings Management topics grew significantly from 2019 to 2025, with the most notable increase occurring in 2022. The most frequently used theories in these studies include stakeholder theory, legitimacy theory, and agency theory, which are generally used as a basis to explain the motivation of companies in disclosing their ESG performance. This study makes an important contribution to academic literature and business practice, and provides relevant insights for future research development in the Environmental, Social, and Governance (ESG) and Earnings Management domains.